Respuesta :
For this case, we have that the equation of the position is given by:
[tex]s (t) = 3 - 4t [/tex]
To find the velocity, we must derive the equation from the position.
We have then:
[tex]s' (t) = - 4 [/tex]
Then, we evaluate the derivative for time t = 8.
We have then:
[tex]s' (8) = - 4[/tex]
Answer:
the instantaneous velocity at t = 8 is:
[tex]s' (8) = - 4[/tex]
[tex]s (t) = 3 - 4t [/tex]
To find the velocity, we must derive the equation from the position.
We have then:
[tex]s' (t) = - 4 [/tex]
Then, we evaluate the derivative for time t = 8.
We have then:
[tex]s' (8) = - 4[/tex]
Answer:
the instantaneous velocity at t = 8 is:
[tex]s' (8) = - 4[/tex]
Answer: - 4
Explanation:
As the question tells, the instantaneous velocity is the first derivative of the position.
1) position equation given: s(t) = 3 - 4t
2) derivative, v(t) = s'(t)
s'(t) = [ 3 - 4t]' = (3)' - (4t)' = 0 - 4(t') = - 4
3) Then, the velocity is constant (does not depends on t), and its value is - 4.
Explanation:
As the question tells, the instantaneous velocity is the first derivative of the position.
1) position equation given: s(t) = 3 - 4t
2) derivative, v(t) = s'(t)
s'(t) = [ 3 - 4t]' = (3)' - (4t)' = 0 - 4(t') = - 4
3) Then, the velocity is constant (does not depends on t), and its value is - 4.